Legal Liability of Event Organizers in Cases of Song Copyright Infringement: A Study of Decision No. 92/Pdt.Sus-HKI/Cipta/2024/PN Niaga Jkt.Pst - Rusdinah, Rusdinah; Sitorus, Rolib (JUSTISI, 2025)
The purpose of this study is to analyze the effectiveness of legal norms in Law No. 28 of 2014 concerning Copyright and Government Regulation No. 56 of 2021 concerning the Management of Song and/or Music Royalties in guaranteeing the protection of the economic and moral rights of songwriters in the context of live performances, through a case study of Decision No. 92/Pdt.Sus-HKI/Cipta/2024/PN Niaga Jkt.Pst. The method used is normative juridical with a statutory approach, case approach, and conceptual approach which are analyzed qualitatively. The novelty of this study lies in the reconstruction of dual legal liability between performers (singers) and event organizers, as well as the application of Hans Kelsen's theory regarding the separation between legal norms (the should) and reality (being) in music copyright disputes. The results of the study show that there is still an imbalance between regulation and practice; industry players often ignore licensing mechanisms and royalty payments through the National Collective Management Agency (LMKN), and do not include the names of creators or make changes to works without permission. Although the judge in the case granted part of the lawsuit, the recognition of direct licensing practices outside the collective mechanism indicates a regulatory loophole and potential legal uncertainty. In conclusion, the effectiveness of positive law in copyright protection in Indonesia has not yet been fully achieved. Therefore, policy reforms are needed to integrate direct licensing mechanisms into the official legal framework, strengthen the role of the LMKN, and enforce stricter sanctions against moral rights violations, so that legal norms truly become a substantive protection instrument for creators.